Public finances in the European Union: Is convergence sustainable? - Holger Bonin; Bernd Raffelhüschen (Albert-Ludwigs-Universität Freiburg, Institut für Finanzwissenschaft, 1999)
In this paper, we discuss the latest generational accounting results for 12 of the 15 EU member states, which were prepared on behalf of the European Commission by an international team of experts. We proceed as follows: Section 2 summarises the characteristic features of the standardised generational accounting concept on which the computations were based. Section 3 investigates the divergence of the European countries in terms of long-run fiscal sustainability, and attempts to work out the fundamental forces behind this outcome. Section 4 focuses on the long-term state of fiscal policy in Germany and the UK. This seems instructive, since the two states run markedly contrasted public pension systems. Counterfactual experiments are used to assess the potential for more balanced fiscal policy. Section 5 concludes the paper.
urn:nbn:de:bsz:25-freidok-134921
Keywords: E62; H55; 330; Sustainable Public Finances; Generational Accounting; European Union; Finanzpolitik; Konvergenzkriterien; Intergenerative Belastungsrechnung; EU-Staaten; Deutschland; Großbritannien